Spatial dimensions of natural resource decisions: private responses to public resource decisions - Goldbach, Rebecca, author; Davies, Stephen, advisor; Thilmany, Dawn, advisor; Goemans, Christopher, committee member; Weiler, Stephan, committee member (Colorado State University. Libraries, 2012)
This dissertation illustrates how the use of spatial economics, as opposed to non-spatial methods, can enrich economic research related to natural resources decision-making. This research encompasses three distinct, but complementary, papers, based on two datasets that vary in richness and scale, and one data-driven model that will detail how data will need to be collected to inform natural resource infrastructure projects in a developing economy. The first essay uses cutting-edge spatial econometric techniques to evaluate the location decisions of private outdoor recreation providers. Here, I find clustering of outdoor recreation opportunities and that private providers are attracted to areas with existing public outdoor recreation opportunities when making their own location decisions. The second essay focuses on a specific form of privately provided outdoor recreation, agritourism, and again finds that the more existing outdoor recreation, the more agritourism trips will be taken. The second essay uses a hurdle travel cost model and focuses on the demanders, as opposed to the suppliers, of private outdoor recreation. The findings reveal that agritourists gain substantial consumer surplus (with averages ranging from $93 to $465) from their trip, and that the model treatment of multi-destination agritourists impacts the estimated consumer surplus. The first two papers use author-created outdoor recreation measures that are introduced in this dissertation. These measures were created to complement the USDA-Economic Research Service Natural Amenities Index, with input from the creators of the Natural Amenities Index, and have potential to be used in many natural resource and economic development studies as the Natural Amenities Index has been. In contrast to the other essays, the third essay recognizes that spatial relationships can be important in evaluating an economic question, even when dense spatial datasets are not available. The study uses an Equilibrium Displacement Model to evaluate water management and storage policies for a canal system in Afghanistan, a country where war and poverty have damaged infrastructure and made it difficult to collect accurate data. Producers' spatial location on the canal is of key importance to understanding their decisions and the failure to account for these spatial relationships could lead to misinformed policy decisions. The Equilibrium Displacement Model results show that water management and storage policies have different impacts on producers based on their spatial location on the canal. Through the use of three very different models, this dissertation illustrates the importance of incorporating spatial impacts when evaluating policies related to natural resources.
Keywords: equilibrium displacement model; travel cost model; spatial econometrics